A history of laughter: Ishwar Gupta and early modern Bengal - Banerjee, Milinda (Das Gupta, 2009)
With reference chiefly to 19th century Bengali literature
Includes bibliographical references (p. [166]-176)
Keywords: Geschichte 1500-1947; Lachen; Bengalen